To Stay or to Leave? Migrant Workers' Decisions During Urban Village Redevelopment in Hangzhou, China - Jin, Xizan; Ren, Tianzhou; Mao, Nuannuan; Chen, Lili (Frontiers in Public Health, 2021)
As a vital source of the demographic dividend, migrant workers living in urban villages have positively contributed to urban economic development and the improvement of urbanization. Although urban villages have had a great impact on public health due to the shabby environments and poor public safety, the large-scale demolition of the urban villages, the supply of affordable housing for migrant workers has decreased drastically, which may lead to the outflow of many migrant workers and consequently affects the sustainable operations of cities. Therefore, this paper takes Hangzhou as an example to study the impact of urban village redevelopment on migrant workers and their migration decisions during urban village redevelopment process. The finding indicates that migrant workers are significantly impacted by large-scale demolition. 1) The number of affected migrant workers is huge. For example, 657,000 migrant workers who lived in around 178 urban villages are affected in Hangzhou (34,468 households). 2) The increase in rent is obvious. 3) Strong expulsion effect: nearly 1/3 migrant workers will decide to leave the city because of the demolition. Furthermore, our binary logistic regression model suggests that the commuting time, living satisfactory, and the rent affordability are factors significantly affecting migration workers’ decision to leave and stay in the city. The housing quality and comfort indicators are not significant. This indicates that convenience for employment and high rent avoidance are the major characteristics of migrant workers’ housing choice. Hence, in addition to considering whether the harsh environment is harmful to the public health of urban and residents, the interest and characteristics of migrant workers should be considered during the current urban village demolition process. While simply demolishing urban villages, government needs to provide a relatively sufficient amount of low-cost and affordable housing for migrant workers in case migrant workers leave the city in large numbers due to lack of suitable housing in the city.